The Use and Limitations of the Single-Level Model for the Electronic Transport in Single-Molecule Contacts - Kilibarda, Filip (My University, 2021)
The field of molecular electronics is seen as one of the candidates for the future beyond Moore scaling efforts. Still, not so many useful examples of working molecular circuits have been produced to this date. This generally stems from the problems with designing the molecular components with the right properties, as well as with their interconnection and integration in the current manufacturing processes. Any attempt to resolve these problems should start with characterizing suitable molecular candidates, and further understanding underlying processes present during molecular binding and electron transport through the molecule. To characterize molecular systems, we use mechanically controllable break junctions (MCBJ). The thesis starts with an in-depth discussion of the experimental setup, measurement procedures, as well as a brief overview of the theoretical background governing mesoscopic transport. Further, the thesis is structured around three different focal points. Firstly, we explore salen-based molecular compounds in an attempt to build components with easily tunable properties. We observe how different metal ions can be used to induce shifts in energy levels of the molecular complex and subsequently form an alternative to classical doping of silicon-based components. Secondly, we analyze the evolution of binding behavior depending on the distance between the leads to which the molecule is coupled. This enables us to understand better how the molecules couple to the mesoscopic conductors. We present results obtained during the measurements and then make an attempt to replicate the present behavior with the help of molecular simulations. And lastly, to efficiently characterize compounds and compare different candidates, we present additional measurements performed on C60 molecule and show how we can use machine learning and statistical methods to extract features from large measurement datasets and compare different compounds. Additionally, we consider how these methods can help us in developing new theoretical prediction models. Equipped with efficient evaluation techniques and the knowledge of how metal ion inclusions and the inner structure of contacts can influence the behavior of the molecule in the junction, we are one step closer to true molecular circuits.
Keywords: MCBJ, Single-Level Model, Salen, C60, Electronic Transport, Binding Mechanism, Machine Learning; 530; 72.80.-r; 73.23.Ad; 73.63.−b; 73.63.Rt; 81.07.−b; 85.65.+h